1987
DOI: 10.1246/cl.1987.203
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Photoallylation of Furyl and Thienyl Dicyanoethenes by Allylic Stannanes via Photoinduced Electron Transfer

Abstract: Irradiation of 1,1-dicyano-2-(2-furyl)ethene and allyltributylstannane in the presence of phenanthrene in aqueous acetonitrile afforded regioselectively 5,5-dicyano-4-(2-furyl)-1-pentane. Photoreactions of the other furyl and thienyl dicyanoethene derivatives with allylic stannanes gave the corresponding allylic products in good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Photoinduced electron transfer (PET) reaction between organosilicon compounds and electron-deficient molecules is a powerful tool for organic synthesis [1][2][3][4][5][6][7][8][9][10][11]. In these photoreactions, radical anions generated from the electron-deficient molecules and carbon radicals generated from radical cations of the organosilicon compounds are postulated as reactive intermediates.…”
Section: Introductionmentioning
confidence: 99%
“…Photoinduced electron transfer (PET) reaction between organosilicon compounds and electron-deficient molecules is a powerful tool for organic synthesis [1][2][3][4][5][6][7][8][9][10][11]. In these photoreactions, radical anions generated from the electron-deficient molecules and carbon radicals generated from radical cations of the organosilicon compounds are postulated as reactive intermediates.…”
Section: Introductionmentioning
confidence: 99%
“…The thus-formed alkylated derivatives were isolated by bulb-to-bulb distillation or by column chromatography. Extending the previously reported initial attempt,3a the reaction was tested with various alkenes, such as methyl acrylate ( 1a ), methyl crotonate ( 1b ), acrylonitrile ( 1c ), and dimethyl maleate ( 1d ). Under these conditions irradiation with tetrabutylstannane ( 2 ) gave the corresponding alkylated derivatives 3a − d in medium to good yield (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…Although back-electron transfer cuts down the lifetime of the thus-formed radical ion pair, fragmentation of the radical cation is sufficiently fast in a number of cases to give neutral alkyl radicals with a reasonable (0.1 or higher) quantum yield. , In turn, the radical is trapped by the long-lived nitrile radical anion, and aromatic substitution is the final result (Scheme , path a). However, the radical can also add to a neutral trap, and indeed, we recently showed that radicalic alkylation of electron-withdrawing substituted alkenes can be obtained under this condition, with the aromatic nitrile (or alternatively an aromatic ester, in this case via the triplet state) functioning as a nonconsumed sensitizer , path b, represents a novel redox sequence for radicalic alkene alkylation in which the educt radical is generated through an oxidative step and the final product arises from the adduct radical via a reductive step 3a.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…,1985h, , 1988a. Similarly, lI1-dicyano-2-(2-thienyl or 2-fury1)ethylenes are photoallylated with allyltrimethylstannane to give 2allylated products in good yields (Mizuno et al, 1987a(Mizuno et al, , 1987b. Irradiation of ArCH,M(CH& (Ar = phenyl, naphthyl and 9-phenanthryl; M = Si, Sn, and Ge) in the presence of Cu(I1) salt in methanol gives the corresponding arylmethyl methyl ethers, products arising from leoxidation of arylmethyl radicals by Cu(I1) ion (Mizuno et al, 1988b).…”
Section: Application To Organic Synthesismentioning
confidence: 99%